Probiotic post feed restriction supplementation on realimentation performances, carcass characteristic, gut morphology and gut microbes of broiler chicken - Razieh Valipourian; Farid Shariatmadari; Hamed Ahmadi; Mohammad Amir Karimi Torshizi (Journal of Applied Poultry Research)
Summary: This study investigated the impact of probiotic (Protexin) supplementation on growth performance, economic cost, and carcass components of broiler chickens during compensatory growth following feed restriction. A total of 384 one-day-old male broiler chicks (Arian) were randomly assigned to four treatment groups with 6 replicate cages and 16 broiler chickens per cage. The treatment structure followed a 2 × 2 factorial arrangement with the main factors being feed restriction (without restriction and 15% restriction) from days 10 to 18 and two subgroups of feeding (no additive and probiotic) from days 18 to 42. Results showed no interactive effects of general performance observed in all. Birds on the probiotic supplementation (PS) diet had significantly higher weight and greater weight gain (WG) in the post-restriction period (days 18-42). Feed efficiency of birds from days 18 to 42 was lower in birds with restricted access to feed from days 10-18 of age. Apart from abdominal fat, which was decreased by FR and PS, no other carcass components or organ weights were affected by the treatments. The ileal microbiota of the broilers was affected by feed restriction at the end of the restriction period (day 18) and PS reduced E. coli and increased Lactobacillus by day 42. Villus height increased in both jejunum and ileum with PS (P > 0.05). Feed restriction and PS supported the performance of broiler chickens during realimentation; however, the interactive effects of those are not significant under the current conditions.